Novel enzymological profiles of human 11beta-hydroxysteroid dehydrogenase type 1. - Hult, M; Nobel, C; Abrahmsen, L; Nicoll-Griffith, D; Jörnvall, H; Oppermann, U (2001)
The human enzyme 11beta-hydroxysteroid dehydrogenase (11beta-HSD) catalyzes the reversible oxidoreduction of 11beta-OH/11-oxo groups of glucocorticoid hormones. Besides this important endocrinological property, the type 1 isozyme (11beta-HSD1) mediates reductive phase I reactions of several carbonyl group bearing xenobiotics, including drugs, insecticides and carcinogens. The aim of this study was to explore novel substrate specificities of human 11beta-HSD1, using heterologously expressed protein in the yeast system Pichia pastoris. In addition to established phase I xenobiotic substrates, it is now demonstrated that transformed yeast strains catalyze the reduction of ketoprofen to its hydroxy metabolite, and the oxidation of the prodrug DFU-lactol to the pharmacologically active lactone compound. Purified recombinant 11beta-HSD1 mediated oxidative reactions, however, the labile reductive activity component could not be maintained. In conclusion, evidence is provided that human 11beta-HSD1 in vitro is involved in phase I reactions of anti-inflammatory non-steroidal drugs like ketoprofen and DFU-lactol.